Argentina : Gender Equity in the Private Sector - World Bank (World Bank, 2012)
First tested in Mexico in 2003, and most recently applied in 2009 in Argentina, the World Bank has developed a model to incorporate gender equity into private sector organizations while simultaneously enhancing their business. Under the model, participating organizations conduct a self-diagnosis to identify gender biases and gaps in the operations. This baseline is then used to create and subsequently implement an action plan to address these gender inequalities in their organization. Successful application of this gender equity model is certified by an independent auditing agency and the firm is awarded a seal they can publicly use and display, enhancing their reputation. Since the first experience in Mexico, the model has been adapted to fit other countries' realities, and each experience has improved the tools and process of the model. This paper summarizes the World Bank's experiences with the gender equity certification model and explores the primary features and factors of success through careful examination of the most recent application in Argentina. The successful experiences and ease of adaptability of the model point towards the feasibility of applying this model as standard World Bank "brand" certifiable international Gender Equity Model, or "GEM".